Development of Learning Module Flipbook with STEAM Approach in Philosophy Course Education - Ekaputra, Firdiawan; Fuldiaratman, Fuldiaratman; Syahri, Wilda (PT ARRUS Intelektual Indonesia, 2024)
The purpose of this study was to develop a learning module flipbook with a STEAM approach in the philosophy of education course. The method used in this research is the Research and Development method. The development model used in this study, namely the ADDIE model which consists of 5 stages including analysis, design, development, implementation, and evaluation. Learning module flipbook media products with the STEAM approach that have been developed are then assessed by media experts and material experts to determine the validity of the media that has been developed. After the developed media is declared feasible to be carried out to the next stage, the feasibility test stage is carried out by students. The subjects used in the product feasibility test in this study were 5 students of the Jambi University Chemistry Education Study Program who had taken the philosophy of education course in the product feasibility test. Based on the results of the product feasibility test assessment, the learning module flipbook with the STEAM approach in the philosophy of education course obtained a score of 90.71 with very good criteria.